2022-RA-998-ESGO Intermediate-risk endometrial cancer: isolated tumor cells (ITC) versus node-negative in sentinel lymph node mapping. An international multi-institutional comparative study. (20th October 2022) - Cucinella, Giuseppe; Schivardi, Gabriella; Zhou, Xun Clare; Alhilli, Mariam; Wallace, Sumer; Wohlmuth, Christoph; Baiocchi, Glauco; Tokgozoglu, Nedim; Raspagliesi, Francesco; Buda, Alessandro; Zanagnolo, Vanna; Zapardiel, Ignacio; et al.
Abstract : Introduction/Background: The clinical impact of isolated tumor cells (ITC) (≤0.2 mm) in sentinel lymph nodes (SLN) of endometrial cancer (EC) is unclear. This study compared the recurrence-free survival (RFS) of intermediate-risk EC patients who underwent SLN biopsy and were node-negative vs. those who had ITC. Methodology: Patients with SLN-ITC, between 2012 and 2019, were identified from 21 centers worldwide, while SLN-node-negative patients were identified from Mayo Clinic, Rochester, between 2013 and 2018 and served as comparing group. Only patients with uterine-confined EC and intermediate-risk factors [grade 1 or 2 endometrioid and myometrial invasion (MI) ≥50%; grade 3 endometrioid and MI <50%; non-endometrioid without MI] were included. Adjuvant therapy (ATx) included vaginal brachytherapy (VB), external beam radiation and/or chemotherapy (EBRT±CHT). The primary outcome was non-vaginal recurrence (hematogenous, peritoneal or lymphatic). Results: Of 200 patients included, 74 had ITC and 126 were node-negative. Sixteen patients had a non-vaginal recurrence and the median follow-up for patients without recurrence was 2.9 (IQR, 1.8–3.8) and 2.8 (0.8–4.4) years for the two groups, respectively. Among the 162 patients with ATx (VB only=112; EBRT±CHT=50), there was no significant difference in non-vaginal RFS between ITC vs. node-negative patients [p=0.34; 4-year RFS 84.1% (95% CI, 72.1–98.1%) vs. 91.5% (95% CI, 84.1–99.4%) for 61 ITC vs. 101 node-negative]. However, we observed worse non-vaginal RFS in the subgroup of 32 patients with concurrent ITC and LVSI (p=0.006, figure 1 ). In particular, the 4-year RFS was 64.6% (95% CI, 43.2–96.8%) in this subgroup compared to 93.3% (95% CI, 81.5–100%) and 91.7% (95% CI, 83.9–100%) for the node-negative patients with and without LVSI, respectively. There were no recurrences among 29 patients with ITC and no LVSI. Conclusion: Our results on intermediate-risk EC, who received ATx, suggest that the simultaneous presence of ITC and LVSI is associated with a poorer prognosis. Further studies are warranted.